Information seeking behaviour of electronic records management systems (ERMS) users: implications for records management practices - Part 1. - Singh, Pauline; Klobas, J.; Anderson, K. (Records Management Association of Australia RMAA, 2007)
This article is the first in a multi-part report on whether the way RM professionals manage records in accordance with the ISO 15489 standard is consistent with the information seeking behaviour (ISB) of Electronic Document and Records Management Systems (EDRMS) users, and includes an investigation of how various factors, such as training, individual information seeking styles, tasks, and time, affect the ISB.